Experimental Penetration Testing Teaching and Learning for High School Students Using Cloud Computing - Contreras Vargas, Berioska (My University, 2019)
The need for high school students trained in ICT to developing cybersecurity skills implies the understanding of threats on security. Considering that the aim of hacking is to circumvent restrictions, the goal of this experimental course is to train students in understanding hacking to improve security. Currently, the reality of hacking has alarmingly evolved and shaped an undeniable black market of information where talented teenagers are not exempt to partake. Despite the fact that the formal teaching and learning of hacking inside high schools can be seen as miseducation, that misunderstanding is faced in this work by addressing both the defensive and offensive security from the perspective of penetration testing. By developing progressive challenges over an adaptive cloud environment, the students can be taught hacking from a constructive perspective. A cloud-based attack surface is implemented which consists of a set of systems gradually prepared by means of scripts. The theoretical and practical lessons are directed by a set of scaffolded and constructivist challenges. The discussion about ethics is confronted and remains present throughout the teaching and learning process. Finally, the results and empirical findings of the students are analyzed and measured demonstrating that high school students can acquire skills to protect information for the community, and for themselves.
Keywords: penetration testing, hacking, teaching and learning, progressive learning, high school, cloud computing